Perception of nurse prescribing among nurses and psychiatrists in a developing country: A cross‐sectional survey. (28th August 2017) - Badnapurkar, Ashish; Bressington, Daniel; Jones, Martin; Nelson, Deborah; Thomas, Dona; Mehndi, Mohammed; Gray, Richard
Abstract: Nurse prescribing has the potential to improve patients' access to, and experiences of, treatment. The aim of the present study was to examine nurse and psychiatrist attitudes about this extended role in a developing country. We conducted a cross‐sectional survey using a previously‐used, 65‐item, seven subscale measure of attitudes to nurse prescribing in mental health. We achieved a 79% response rate. The majority of participants had trained in developing countries where nurse prescribing has yet to be implemented. Across five subscales (general beliefs, impact, uses, training, and supervision), both groups reported positive attitudes about nurse prescribing. Both groups scored the training subscale particularly highly. Compared with psychiatrists, nurses were more confident about the range of clinical settings where nurse prescribing could be applied (e.g. acute inpatient and substance use). Although both groups had less favourable attitudes on the two subscales relating to clinical and legal responsibility, compared to nurses, psychiatrists were more undesirable. Although, overall, clinician attitudes do not seem to represent a barrier towards the potential implementation of nurse prescribing in the study setting, clarity about clinical and legal responsibility needs to be addressed.